2008
DOI: 10.2147/vhrm.s1839
|View full text |Cite
|
Sign up to set email alerts
|

Vascular risk factors, cognitve decline, and dementia

Abstract: Dementia is one of the most important neurological disorders in the elderly. Aging is associated with a large increase in the prevalence and incidence of degenerative (Alzheimer's disease) and vascular dementia, leading to a devastating loss of autonomy. In view of the increasing longevity of populations worldwide, prevention of dementia has turned into a major public health challenge. In the past decade, several vascular risk factors have been found to be associated with vascular dementia but also Alzheimer's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(62 citation statements)
references
References 205 publications
4
53
1
4
Order By: Relevance
“…Previous studies have demonstrated a relationship between CVR factors and cognitive functioning (Duron & Hanon, 2008;Knopman et al, 2001). The lack of such association in this study can be explained by methodological and conceptual factors.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…Previous studies have demonstrated a relationship between CVR factors and cognitive functioning (Duron & Hanon, 2008;Knopman et al, 2001). The lack of such association in this study can be explained by methodological and conceptual factors.…”
Section: Discussioncontrasting
confidence: 70%
“…By choosing a nonweighted method for the computation of cardiovascular factors, we may have overlooked some important distinctions in the relative influence of each medical condition on cognitive performance. Some conditions, such as diabetes and hypertension, appear to be stronger independent predictors of cognition (Duron & Hanon, 2008;Kuo et al, 2005) than others, such as elevated waist circumference (Chu et al, 2009;Dore, Elias, Robbins, Budge, & Elias, 2008), which was very prevalent in our sample. Yet, they all contributed equally to the total score.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…CT is therefore best viewed as only part of a wider strategy of maximal risk reduction and maintenance of optimal brain health. CT complements and should be combined with other risk reduction strategies, including participation in cognitive, social, and physical leisure activities [45,46], as well as careful control of vascular risk factors [47].…”
Section: Clinical Recommendationsmentioning
confidence: 99%
“…Furthermore, SAH is associated with subtle neurocognitive deficits [22,23] which may be potentiated by one's lifestyle, like obesity [24], smoking [25], sedentary behavior [26], stress [27] and may further increase the risk of dementia [28]. Taken together, this background is associated with an increased chance SAH individuals have for developing vascular dementia, especially those who have been exposed to this condition for years [29].…”
Section: Systemic Arterial Hypertension and Cognitive Functionmentioning
confidence: 99%